(untitled) (ENVIRONMENT. TECHNOLOGY. RESOURCES. Proceedings of the International Scientific and Practical Conference, 2015)
Lignosilicon (LSi), a plant growth activator, was synthesized at the Latvian State Institute of Wood Chemistry (LS IWC) on the basis of the wood lignocellulosic complex. It is shown that LSi, used for treatment of potato tubers before sowing at low application rates of 20-40 kg/ha, has a favourable action on the yield and quality of the tubers. In comparison with the control, the additional yield achieved on the background of LSi (20-40 kg/ha) was 18-20%. The best biochemical composition was for the tubers wetted with water and LSi-treated before the sowing, i.e., the content of dry matter and starch increased by 16% and 18%, respectively, but the content of nitrates in the tubers decreased 1.6 times. LSi can be recommended for potato cultivation under conditions of conventional and organic agriculture.